Impact of glucocorticoids on systemic sirtuin 1 expression and activity in rats with adjuvant-induced arthritis. Issue 2 (1st February 2021) - Pasquereau, Sébastien; Totoson, Perle; Nehme, Zeina; Abbas, Wasim; Kumar, Amit; Verhoeven, Frank; Prati, Clément; Wendling, Daniel; Demougeot, Céline; Herbein, Georges
ABSTRACT: The class III histone deacetylase sirtuin 1 (SIRT1) plays a pivotal role in numerous biological and physiological functions, including inflammation. An association between SIRT1 and proinflammatory cytokines might exist. In addition to their important role in inflammation associated with rheumatoid arthritis (RA), proinflammatory cytokines mediate the development of systemic effects. Here, we evaluated systemic SIRT1 expression and enzymatic activity, in peripheral blood mononuclear cells (PBMCs) and in liver isolated from rats with adjuvant-induced arthritis (AIA), treated or not with low or high doses of glucocorticoids (GCs). We also measured the production of tumour necrosis factor alpha (TNF) and interleukin-1 beta (IL-1 beta) in PBMCs and liver. We found that SIRT1 expression and activity increased in PBMCs of AIA rats compared to healthy controls and decreased under GC treatment. Similarly, we observed an increased SIRT1 activity in the liver of AIA rats compared to healthy controls which decreased under high doses of GCs. We also found an increase in IL-1 beta and TNF levels in the liver of AIA rats compared to healthy controls, which decreased under high doses of GC. We did not observe a significant correlation between SIRT1 activity and proinflammatory cytokine production in PBMC or liver. In contrast, a strong positive correlation was found between the liver levels of TNF and IL-1 beta (rho=0.9503, p=7.5x10 −21 ). Our results indicate that increased inflammation in AIA rats compared to healthy control is accompanied by an increased SIRT1 activity in both PBMCs and liver, which could be decreased under GC treatment.